OK, Boomer: New Users, Different Platforms, New Challenges - Romero-Rodríguez, Luis M; Tejedor-Calvo, Santiago; Berlanga Fernández, Inmaculada (Media and communication, 2022)
The popularization of new interaction spaces brings new narratives and social phenomena that merit attention from the sci‐ entific community. Based on the existing literature on the new challenges facing the communication discipline with these emerging narratives, this editorial summarizes the empirical and theoretical contributions of the thematic issue entitled “New Narratives for New Consumers: Influencers and the Millennial and Centennial Generations.” The authors emphasize that the studies selected for this thematic issue explore the innovative features and opportunities of the emerging scenar‐ ios and offer a cautionary account of their structural problems and the urgency of a new media literacy.
Keywords: centennials; digital media; facebook; influencers; instagram; millenials; social networks; online participation; TikTok; YouTube; JCR; Scopus(2)